Neuroscience of aggression - Miczek, Klaus A.; Meyer-Lindenberg, Andreas (Springer Berlin Heidelberg Imprint: Springer, 2014)
This volume assembles the leading aggression researchers both at the preclinical and clinical level. They review the current state of knowledge about neural mechanisms of aggressive behavior and point to the need for innovative methodologies to further our understanding of this greatly understudied set of behaviors.
Description based upon print version of record
Keywords: Aufsatzsammlung; Neurowissenschaften; Aggression; Neuropsychologie; Aggressivität